Attitudes towards immigrants of other race or ethnic origin: Polish dataset from Round 7 of the European Social Survey - Olga Czeranowska (University of Warsaw, Centre of Migration Research (CMR), 2018)
Sociological reflections on attitudes towards members of the out-group (such as immigrants) can be divided into two main strands. The first focuses on intergroup conflict and the second on contact between members of different groups. Intergroup conflict theory seeks to identify causes of prejudice in situations of rivalry, when members of opposite groups are perceived as a threat. By contrast, contact hypothesis assumes that interaction between two groups would lessen prejudice, especially if certain requirements regarding the nature of the contact are met. In this paper we use the Polish dataset from Round 7 of the European Social Survey to analyze factors influencing attitudes towards immigrants of race or ethnic origin that is different than the majority of Poles. Our binary logistic regression model shows that fraternal relative deprivation is the most important factor in predicting respondents' openness to letting immigrants of different race or ethnic origin enter and stay in Poland. The economic situation and education of respondents are also factors, which can be related to their perceptions of realistic threat. 'Basic' contact with individuals who have a different race or ethnic origin is not significant, but having friends from a different race or ethnic group increases the chance of developing positive attitudes regarding immigrants of different race or ethnic origin entering and staying in Poland.
Keywords: 330; immigrants; intergroup attitudes; prejudice